Analisis Tokoh Utama Dalam Cerpen “Banjirkap” Karya Habolhasan Asyari (Kajian Sosiologi Sastra) - Ananda, Anggi Risma Ayu; Arifin, Syaiful; Setyawati, Meita (Adjektiva: Educational Languages and Literature Studies, 2020)
Short story is a form of fiction created by human creativity and imagination that contains ideas about life and is briefly expressed, both in terms of the number of actors, the events narrated, and the overall content of the story. Sociology is a scientific and objective study of humans in society, the study of social institutions and social processes. This study aims to determine the sociology of literature as a reflection of society's literary indicators in the short story of Banjirkap by Habolhasan Asyari and its implications for learning literature in the Indonesian Language and Literature Education Study Program based on Ian Watt's reception theory. The research method used is descriptive qualitative research method. Data collection techniques used are reading techniques and note-taking techniques. The data used in this study are words or sentences in the short story of the Banjirkap by Habolhasan Asyari. The results of this study are in the form of prose structure and literary sociology, literary indicators as a reflection of society. The results obtained from the structure of prose, namely: (a) theme, (b) plot, (c) characters and characterizations, (d) setting. The sociology of literature is as follows: (a) Literature as a mirror of society.